2020
DOI: 10.3126/researcher.v4i1.33814
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between Job Satisfaction, Democratic Leadership Style and the Organizational Commitment of Employees of Privates of Bank in Nepal

Abstract: This study investigated the effect of job satisfaction and perceived democratic leadership style of the managers on the organizational commitment of the employees working in the private banks in Nepal. The population in this study was all employees working in the private banks in Nepal. A hybrid instrument, which comprised pre-tested instruments, was used to collect the data. The analytical method used to test the hypothesis of the research was multiple regression analysis. Statistical Package for Social Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(55 reference statements)
0
1
1
Order By: Relevance
“…No significant relationship was observed between democratic leadership style and commitment. The result of this study contradicted the study findings of various researches that democratic style has a significant relationship and positive effect to commitment of individuals in an organization (Akparep et al, 2019;Al Khajeh, 2018;Diana et al, 2021;Essien & Ekoriko, 2020b;Jony et al, 2019;Rai et al, 2020;Rao & Zaidi, 2020;Setiawan et al, 2021;Matiko & Mbuti, 2021). On the other hand, these findings are from various disciplines; hence, the result of this present study is not yet conclusive.…”
Section: Democratic Leadership Style and Commitmentcontrasting
confidence: 98%
“…No significant relationship was observed between democratic leadership style and commitment. The result of this study contradicted the study findings of various researches that democratic style has a significant relationship and positive effect to commitment of individuals in an organization (Akparep et al, 2019;Al Khajeh, 2018;Diana et al, 2021;Essien & Ekoriko, 2020b;Jony et al, 2019;Rai et al, 2020;Rao & Zaidi, 2020;Setiawan et al, 2021;Matiko & Mbuti, 2021). On the other hand, these findings are from various disciplines; hence, the result of this present study is not yet conclusive.…”
Section: Democratic Leadership Style and Commitmentcontrasting
confidence: 98%
“…In the study of Zaidi and Rao (2020) revealed that there is a significant association between perceived leadership style, specifically democratic approach, to the organizational commitment of Tourism SMEs. Democratic leadership style of the managers as perceived by their employees has a significantly positive impact on their organizational commitment (Rai and Budhathoki, 2020). Assefa (2020) study revealed that there is a significant relationship between democratic leadership style and teachers school commitment.…”
Section: Democratic Leadership Style and Commitmentmentioning
confidence: 99%